The Empirical Analysis of the Quality Level of Tourism Industry Services in Toraja: Ke'te Kesu - Darmawan, Armin; Bahri, Syamsul; Rahman, Irfan (Graduate School, Universitas Brawijaya, 2019)
Indonesia has a number of tourism potentials to be built and developed sustainably. The destinations of local and overseas tourists have experienced an excellent growth trend in recent years, especially in North Toraja District, South Sulawesi. Therefore, the tourism industry is the government's main concern in recent years to increase its index because of its potential to boostthe economic growth, especially for the local people and GDP. This study focused on the empirical analysis of the tourism industry service level that is viewed from the readiness and the support fromavailable infrastructures. The method of this study was a survey distributed to respondents visiting the tourism industry using questionnaire based on SERVQUAL and IPA Diagram. By using Servqual and Important Performance Analysis (IPA) method, found 8 service attributes which were divided into 5 Servqual dimensions indicating that the service quality at Ke'te Kesu, North Toraja Regency, South Sulawesi needs to improve the aspects on Important Performance Analysis (IPA) diagram, including the service attribute T5 (the availability of restaurants around the tourist location), T6 (the availability of street signs to tourist objects), R2 (the ease of finding tourist locations), R3 (the availability of public transportation to tourist location), RE4 (the immediate response from the officer/local citizen on the request or complain), RE5 (tourist information centre, contact person) is clear), A1 (Staffs are expert in serving tourists), and E5 (the concerns of tour operators and officers/residents to the needs of visitors). Keywords: Customer Satisfaction, IPA Diagram, Service Quality, Toraja, Tourism.